Towards fossil-free steel: Life cycle assessment of biosyngas-based direct reduced iron (DRI) production process. (20th March 2023) - Nurdiawati, Anissa; Zaini, Ilman Nuran; Wei, Wenjing; Gyllenram, Rutger; Yang, Weihong; Samuelsson, Peter
Abstract: Given the urgent need for transitions towards global net zero emissions, decarbonisation of the iron and steel industry is critical. Deep decarbonising this sector requires a breakaway from current blast furnace-basic oxygen furnace (BF-BOF) technologies that largely depend on fossil resources. Biosyngas is considered to be a promising alternative to fossil energy and reductants used in existing ironmaking due to its renewability, technological maturity and compatibility for use in existing furnaces. The present work assesses the environmental impacts of biosyngas-based direct reduced iron production followed by electric arc furnace (DRI-EAF) routes for crude steel production. Further, the proposed routes are compared with the other steelmaking routes, including BF-BOF, natural gas (NG)-based and hydrogen-based direct reduction routes by performing life cycle assessment (LCA). The results indicate that the global warming potential (GWP) value for the biosyngas-based DRI-EAF system is 75% lower than the existing NG-based DRI-EAF route and 85% lower than the BF-BOF route. Moreover, the proposed system possibly has lower GWP values than the renewable hydrogen-based DRI-EAF route. The proposed system has an estimated cradle-to-gate GWP of 251 kg CO2 eq./t crude steel, of which 80% is from upstream emissions. Combined with CO2 storage, the GWP of the proposed system is a net negative, estimated at −845 kg CO2 eq./t crude steel for the selected system boundary. In addition to GWP, other non-climate impact indicators are also evaluated to identify potential burden shifting. The results highlight the emissions reduction potential of the novel biosyngas DRI production route. Large-scale deployment, however, requires sustainable forest management and adequate CCS infrastructure, along with a strong, long-term policy framework to incentivise the transitions. Graphical abstract: Image 1 Highlights: The LCA of steel production via biosyngas-direct reduced iron (DRI) route is studied. Scenario analysis considers technical parameters, policy aspect and market dynamic. The climate impact is 75–85% lower than that of conventional fossil-based steel. The biomass supply chain contributes around 20% to the overall climate impact. Climate impact of the proposed system combined with CCS is −0.8 t CO2 eq./t steel.